Kecurangan Laporan Keuangan: Financial Target, Nature Of Industry, Dan Perubahan Auditor Dengan Komite Audit Sebagai Variabel Moderasi (Studi Bursa Efek Indonesia Tahun 2015-2019) - Evie - Sukma; Lestari Daswan (IAIN Kendari, 2023)
This study examines the effect of financial targets, the nature of the industry and auditor changes on financial statement fraud with the audit committee as a moderating variable in manufacturing companies. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange for the period 2015 - 2019. Data collected by purposive sampling obtained as many as 165 company data, which became the research sample. The data used is secondary data in the form of annual reports of companies sampled for research. Data test tools using Eviews software include descriptive statistical analysis, classical assumption test, determination coefficient test, simultaneous significant test, and hypothesis testing. The results showed that the financial target variable positively affected financial statement fraud. The nature of industry variables has no positive effect on financial statement fraud. The audit committee weakens the positive effect of financial targets on financial statement fraud. Audit quality does not weaken the positive effect of the nature of industry variables and auditor changes on financial statement fraud.